Successful Endovascular Management of Recurrent Hemoptysis due to Multiple Rasmussen Aneurysms in a Case of Pulmonary Tuberculosis: A Rare Case Scenario - Devkota, Shritik; Bhujade, Harish; Baloji, Abhiman; Prabhakar, Nidhi; Saroch, Atul; Gorsi, Ujjwal (Acta medica Lituanica, 2024)
Background: Hemoptysis is defined as coughing out of blood. Pulmonary tuberculosis is the most common cause of hemoptysis in tuberculosis-endemic countries like India. Rasmussen aneurysm is a pseudoaneurysm arising from the pulmonary artery adjacent to or within a tuberculous cavity. Chest radiographs, chest computed tomography angiography (CTA), and digital subtraction angiography (DSA) are the imaging tools for evaluating a case of hemoptysis.Case: A 32-year-old man with a history of pulmonary tuberculosis presented with complaints of recurrent hemoptysis. On imaging evaluation, multiple pulmonary artery pseudoaneurysms were seen in the left lung. The patient was shifted to the DSA lab and the pseudoaneurysms were subsequently treated by endovascular coil embolization. Hemoptysis resolved following the procedure and the patient was again started on anti-tubercular therapy.Conclusion: Endovascular coiling is minimally invasive, safe, and effective management of multiple Rasmussen aneurysms for preventing possible torrential blood loss and unfortunate death.
Keywords: Rasmussen aneurysm; pulmonary tuberculosis; pulmonary artery pseudoaneurysm; coil embolization